Evolution of ASPM coding variation in apes and associations with brain structure in chimpanzees. (11th June 2019) - Singh, Sheel V.; Staes, Nicky; Guevara, Elaine E.; Schapiro, Steven J.; Ely, John J.; Hopkins, William D.; Sherwood, Chet C.; Bradley, Brenda J.
Abstract: Studying genetic mechanisms underlying primate brain morphology can provide insight into the evolution of human brain structure and cognition. In humans, loss‐of‐function mutations in the gene coding for ASPM (Abnormal Spindle Microtubule Assembly) have been associated with primary microcephaly, which is defined by a significantly reduced brain volume, intellectual disability and delayed development. However, less is known about the effects of common ASPM variation in humans and other primates. In this study, we characterized the degree of coding variation at ASPM in a large sample of chimpanzees (N = 241), and examined potential associations between genotype and various measures of brain morphology. We identified and genotyped five non‐synonymous polymorphisms in exons 3 (V588G), 18 (Q2772K, K2796E, C2811Y) and 27 (I3427V). Using T1‐weighted magnetic resonance imaging of brains, we measured total brain volume, cerebral gray and white matter volume, cerebral ventricular volume, and cortical surface area in the same chimpanzees. We found a potential association between ASPM V588G genotype and cerebral ventricular volume but not with the other measures. Additionally, we found that chimpanzee, bonobo, and human lineages each independently show a signature of accelerated ASPM protein evolution. Overall, our results suggest the potential effects of ASPM variation on cerebral cortical development, and emphasize the need for further functional studies. These results are the first evidence suggesting ASPM variation might play a role in shaping natural variation in brain structure in nonhuman primates. Abstract : ASPM coding variation is potentially associated with cerebral ventricular volume in chimpanzees.